Two cases of Fabry disease identified in brothers - Ji Eun Cho; Yong Hee Hong; Yang Gyun Lee; Han Wook Yoo; Dong Hwan Lee (Korean Pediatric Society, 2010)
Fabry disease is a rare, X-linked inborn error of glycosphingolipid catabolism caused by a mutation in the gene encoding the ?#7015;alactosidase A (GLA) enzyme. We report two cases of Fabry disease in a 12-year-old boy who had acroparesthesia and in his elder brother with milder symptoms who were diagnosed by GLA activity assays and the presence of the GLA gene mutation.